Language Crimes in the Form of Threats at the Gorontalo Regional Police and Their Implications for Indonesian Language Learning in High Schools - Elastri Bahutala; Supriyadi; Asna Ntelu (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms of language crimes (word groups and clauses) of threats in the Gorontalo Regional Police; describe the function of language crimes in the form of threats in the Gorontalo Regional Police; describe the meaning of language crimes in the form of threats in the Gorontalo Regional Police; and how the results of this study are implied in Indonesian language learning in high schools. This study uses a qualitative descriptive method of case study type with a forensic linguistic approach. The research data sources are official documents in the form of data recaps of language crime cases containing threats from the Gorontalo Regional Police and its relatives (Gorontalo City Police, Bone Bolango Police, and Gorontalo Resort Police) during a certain period. The data were analyzed systematically through the stages of data reduction, data presentation, and drawing conclusions, using pragmatic theory to analyze function and meaning. The results of the study show that from 11 cases of language crimes in the form of threats in the Gorontalo Regional Police, namely 7 word groups, namely